2021
DOI: 10.3390/ijerph18041686
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Preventive Outreach Targeting Dental Caries and Oral-Health-Related Quality of Life for Refugee Children

Abstract: Objective: The study assessed a preventive outreach educational intervention targeting improvements in dental caries and oral-health-related quality of life in the children of refugee families by comparing pre- and postintervention outcomes. Methods: This randomized controlled clinical trial assessed the outcomes at baseline and three times over six months using the WHO oral health assessment form (DMFT/dmft) and the parent version of the Michigan Oral-Health-Related Quality of Life scale. Children and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Two researchers screened and evaluated the full text of 20 articles, and finally 15 articles were included (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 3, all the included studies were within the triangle area, and no obvious bias was observed (Figure 3).…”
Section: The Included Studiesmentioning
confidence: 99%
“…Two researchers screened and evaluated the full text of 20 articles, and finally 15 articles were included (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 3, all the included studies were within the triangle area, and no obvious bias was observed (Figure 3).…”
Section: The Included Studiesmentioning
confidence: 99%
“…The dt was 2.54 ± 3.6, mt was 0.05 ± 0.3 and the ft was 0.03 ± 0.2. 16% had a pufa index greater zero Alrashdi et al (2021) [ 76 ] USA Multiple countries Randomised control trial 100 interventions and 100 controls 0–12 years Parents and children refugees The DMFT/dmft score increased from baseline to six months after educational intervention (0.28; 95% CI: 0.06, 0.50; p = 0.012) and did not differ significantly from those who sis not receive intervention (β = −0.23, 95% CI: (− 0.57, 0.11; p = 0.18) Bhusari et al (2020) [ 77 ] Multi-country Multiple countries Systematic review Varies by study Refugees Caries prevalence ranged between 50% and 100%. Prevalence was proportional to age, inversely associated with education and not significantly associated with gender and country of origin Werneck et al (2008) [ 78 ] Canada Multiple countries Case-control 52 ECC cases and 52 controls Refugees mean (SD) age = 32.4 (11) months The strongest predictors of ECC in this immigrant population were lack of dental care (AOR = 3.96, 95%CI: 1.34, 11.70) and lack of dental insurance (AOR = 4.87, 95%CI: 1.85, 12.82).…”
Section: Methodsmentioning
confidence: 99%
“…Second, previous studies on health education that used experimental design and analyzed the impact of health education on knowledge, attitude, and behaviors also did not analyze the relationship between knowledge, attitude, and behavior. 41 , 46 , 47 …”
Section: Methodsmentioning
confidence: 99%